2009
DOI: 10.1177/1362361309105659
|View full text |Cite
|
Sign up to set email alerts
|

The role of vision for online control of manual aiming movements in persons with autism spectrum disorders

Abstract: Recent studies suggest motor skills are not entirely spared in individuals with an autism spectrum disorder (ASD). Previous reports demonstrated that young adults with ASD were able to land accurately on a target despite increased temporal and spatial variability during their movement. This study explored how a group of adolescents and young adults with an ASD used vision and proprioception to land successfully on one of two targets. Participants performed eye movements and/or manual reaching movements, either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
104
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 36 publications
21
104
1
Order By: Relevance
“…The difference between the hand and direction manipulated conditions may also be linked to reports of reduced functional connectivity between brain areas as well as to reduced connectivity between hemispheres via the corpus callosum (Just et al 2007;Nyden et al 2004). Inefficient or varied connectivity between brain areas is also consistent with the present finding that individuals with autism experienced greater variability in the execution of their movements as well as previous reports of increased spatial variability during the execution of manual aiming movements (Glazebrook et al 2006(Glazebrook et al , 2009. However, the variability of movement initiation processes was equal to or less than the participants without autism when the longer mean reaction times were accounted for.…”
Section: Discussionsupporting
confidence: 85%
“…The difference between the hand and direction manipulated conditions may also be linked to reports of reduced functional connectivity between brain areas as well as to reduced connectivity between hemispheres via the corpus callosum (Just et al 2007;Nyden et al 2004). Inefficient or varied connectivity between brain areas is also consistent with the present finding that individuals with autism experienced greater variability in the execution of their movements as well as previous reports of increased spatial variability during the execution of manual aiming movements (Glazebrook et al 2006(Glazebrook et al , 2009. However, the variability of movement initiation processes was equal to or less than the participants without autism when the longer mean reaction times were accounted for.…”
Section: Discussionsupporting
confidence: 85%
“…parameters referring to joint motions and angles at specific points in a movement and typically reported in terms of the velocity, acceleration (change in velocity) and jerk (change in acceleration) of a particular point on the body. Such studies have revealed differences between autistic and typical individuals [39][40][41][42][43][44][45].…”
Section: (D) Upper Limb Movementsmentioning
confidence: 99%
“…To illustrate, Glazebrook et al [41,42] found that adults with autism required more time both during movement initiation and execution for manual aiming movements, while Rinehart and colleagues have reported that autistic children [40] and young adults [46] require more time to prepare point-to-point movements (moving from one point in space to another). Further work uses the reach-to-grasp task where, upon presentation of a cue, participants move their hand from a start position to grasp a target object.…”
Section: (D) Upper Limb Movementsmentioning
confidence: 99%
“…Motor skills are highly important for effective communication and social interaction thus causing it to perhaps be one of the main factors behind autistic children finding it difficult to conform to the norm of social interactions in today's society [5]. A study was conducted by Cheryl Glazebrook et al [6] on the sort of motor delays evident in ASD. Individuals were required to perform hand and eye movements simultaneously and then separately.…”
Section: Introduction a Autism Spectrum Disordermentioning
confidence: 99%